2013
DOI: 10.1186/1471-2431-13-139
|View full text |Cite
|
Sign up to set email alerts
|

Pain management policies and practices in pediatric emergency care: a nationwide survey of Italian hospitals

Abstract: BackgroundPain experienced by children in emergency departments (EDs) is often poorly assessed and treated. Although local protocols and strategies are important to ensure appropriate staff behaviours, few studies have focussed on pain management policies at hospital or department level. This study aimed at describing the policies and reported practices of pain assessment and treatment in a national sample of Italian pediatric EDs, and identifying the assocoated structural and organisational factors.MethodsA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…4 This variation mirrors inconsistent practices seen in emergency departments regarding the treatment of procedural pain in children. 21,22 Though the children seen in the outpatient lab were generally well at the time of their venipuncture, the experience of a needle stick for outpatient venipuncture is similar to that of children undergoing venipuncture in the emergency department. Similarly, the act of using a needle to obtain blood is less invasive but similar to the placement of an IV catheter.…”
Section: Discussionmentioning
confidence: 99%
“…4 This variation mirrors inconsistent practices seen in emergency departments regarding the treatment of procedural pain in children. 21,22 Though the children seen in the outpatient lab were generally well at the time of their venipuncture, the experience of a needle stick for outpatient venipuncture is similar to that of children undergoing venipuncture in the emergency department. Similarly, the act of using a needle to obtain blood is less invasive but similar to the placement of an IV catheter.…”
Section: Discussionmentioning
confidence: 99%
“…The management of pain and anxiety in children undergoing medical procedures is a significant clinical issue; even minor procedures can lead to significant distress . Recent studies have reported that management of procedural pain in children is often suboptimal . Inadequate management of pain during a procedure can lead to the formation of an association between pain and the procedure, which can lead to the development of fear and anxiety related to the procedure and an aversion to medical care .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recent studies have reported that management of procedural pain in children is often suboptimal. [3][4][5] Inadequate management of pain during a procedure can lead to the formation of an association between pain and the procedure, which can lead to the development of fear and anxiety related to the procedure and an aversion to medical care. [6][7][8][9] Enhanced anxiety related to a procedure can in turn exacerbate the perception of pain from a procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Parents' misconceptions on the tolerance, side effects and addiction of analgesics (Finley, Kristjansdottir, & Forgeron, 2009;Lim et al, 2012;Rony, Fortier, Chorney, Perret, & Kain, 2010) can lead to inadequate uses of pain medication for their children (Voepel-Lewis, Zikmund-Fisher, Smith, Zyzanski, & Tait, 2015), especially when conflicting symptoms like high pain and an adverse effect are present (Longard et al, 2016;Voepel-Lewis et al, 2015). This might be one of the reasons why children's postoperative pains are undertreated (Avian et al, 2016;Chieng et al, 2013;Ferrante et al, 2013;Twycross & Collins, 2013b).…”
Section: Introductionmentioning
confidence: 99%